The effect of propolis on CCL5 and IFN-gamma expression by peripheral blood mononuclear cells from leishmaniasis patients - Amarante, Marla Karine; Ehara Watanabe, Maria Angelica; Conchon-Costa, Ivete; Fiori, Leandra Lopes; Maeda Oda, Julie Massayo; Bufalo, Michelle Cristiane [UNESP]; Sforcin, Jose Mauricio [UNESP] (Wiley-Blackwell, 2012)
Objectives Mucocutaneous leishmaniasis is associated with a strong Th1 immune response to Leishmania, which modulates chemokines and their receptors expression, affecting their migratory capacity. There are no antileishmanial vaccines available and chemotherapy still relies on the potentially toxic pentavalent antimonials. Propolis is a bee product with immunomodulatory and antiparasite activities, and researchers have been attracted to its potential for the development of new drugs. This work investigated the effects of propolis on CCL5 and IFN-? expression by peripheral blood mononuclear cells (PBMC) in order to evaluate a possible immunomodulatory action of propolis in patients with leishmaniasis compared to healthy control subjects.Methods PBMC were incubated in the absence or presence of propolis and the evaluation of a possible cytotoxicity of propolis was carried out using MTT assay. The expression level of CCL5 and IFN-gamma was determined by real-time PCR.Key findings Our data indicated that propolis modulates the immune response of leishmaniasis patients in vitro, affecting CCL5 and IFN-gamma expression by PBMC.Conclusions Data suggested that propolis drives an anti-inflammatory response depending on concentration. Although propolis is a potential source of new and selective drugs for the treatment of leishmaniasis, its usefulness in the therapeutics should be further investigated.
Keywords: CCL5; IFN-gamma, Leishmania; propolis